Effect of structural manipulation in hetero-tri-aryl amine donor-based D–A′–π–A sensitizers in dye-sensitized solar cells. (21st February 2018) - Patil, Dinesh S.; Sonigara, Keval K.; Jadhav, Manoj M.; Avhad, Kiran C.; Sharma, Suryapratap; Soni, Saurabh S.; Sekar, Nagaiyan
Abstract : Modification of a triarylamine donor group along with variation in the anchoring groups could finely manipulate the photophysical property and tuning the behaviour of D–A′–π–A sensitizers in DSSCs for better efficiency achievement. Abstract : The role of hetero-atom manipulation/hetero-aryl group insertion in the triarylamine to obtain hetero triarylamine as a donor in highly efficient photosensitizers was investigated to study the structure–efficiency relationship in dye-sensitized solar cells (DSSCs). A newly synthesized sensitizer was explored containing N -phenyl- N -(pyridin-2-yl) pyridine-2-amine (DPPA) and N -(pyridin-2-yl)- N -(thiophen-2-yl) pyridine-2-amine (DPTA) as the donor along with a strong electron-withdrawing cyano group (–CN) as the auxiliary acceptor group and cyanoacetic acid and rhodamine-3-acetic acid as anchoring groups. The triphenylamine donor was manipulated for the first time with the insertion of a nitrogen atom in the aryl ring for DSSCs. These hetero-aryl-based sensitizers showed a significant improvement in the photophysical as well as photovoltaic performance. The replacement of cyanoacetic acid by rhodanine-3-acetic acid as an anchoring unit resulted in a significant red-shift in absorption as well as emission maxima. The methylene group in rhodanine-3-acetic acid interrupted the LUMO delocalization on the anchoring group in sensitizersDP3 andDP4, as shown by DFT calculations. The presence of cyanoacetic acid in sensitizersDP1 andDP2 showed effective charge transfer from HOMO to LUMO and efficient electron injection from LUMO to the conduction band of the TiO2 semiconductor. The sensitizerDP2 showed a maximum efficiency of 4.7%, a short-circuit current J sc = 11.78 mA cm −2, an open-circuit voltage V oc = 0.608 V and a fill factor FF = 0.62. The enhanced efficiency of sensitizerDP2 was attributed to the presence of the strong electron-withdrawing cyanoacetic acid anchoring group and the presence of the thiophene linker at the N -aryl core.